Culturally responsive teaching in diverse classrooms: A framework for teacher preparation program - Hamed Ghaemi; Noushin Boroushaki (Australian Journal of Applied Linguistics)
This paper analyses the importance of culturally responsive teaching (CRT) in heterogeneous classrooms and proposes a comprehensive framework for teacher development programmes designed to improve effective instruction for various student groups. As classroom diversity increases, it is imperative to equip pre-service teachers with the requisite knowledge and abilities to cultivate inclusive, culturally responsive learning environments. This study evaluates the influence of CRT principles on student performance and instructor preparedness by examining their integration into teacher education programmes. The investigation employed a mixed-methods approach to collect both qualitative and quantitative data, assessing the perceived impact on student engagement and academic performance, the challenges faced by educators, and the integration of CRT techniques into teacher preparation programmes. The results highlight the necessity of enhancing teachers’ cultural competence, promoting equity literacy, and fostering critical self-reflection to ensure educators are prepared to address the needs of diverse learners. The study provides pragmatic recommendations for improving teacher education, emphasising the necessity of continuous dedication to social justice, equity, and culturally sustaining pedagogy within teacher training programmes. This research contributes to the discourse on adequately equipping teachers to manage the intricacies of diversity in modern classrooms.